Population Administration Service Innovation in Indonesia During the Covid-19 Pandemic - Wisber Wiryanto (Indonesian Association for Public Administration (IAPA), 2020)
The Corona Virus Disease 2019 (Covid-19) pandemic has an impact on changing work patterns around the world. This also includes public services in the population administration (Adminduk) sector in Indonesia. The Ministry of Home Affairs has issued a letter No. 443.1/2978/Dukcapil dated March 16, 2020, concerning Adminduk Services and Virus Corona Diseases (Covid-19) Prevention. This letter was sent to the Head of Population and Civil Registry (Dukcapil) offices in all Province and Regency/City. This letter consists of some instructions to conduct for Adminduk service efficiently and effectively during the Covid-19 pandemic. Therefore, as an implementation this instruction, a study about innovation of Adminduk service during the Covid-19 pandemic to find out innovation by Dukcapil offices. A problem formulation as a research question as follow, what is innovation of Adminduk service can make by Dukcapil offices during the Covid-19 pandemic? The study was conducted in the second quarter of 2020. Research methods using library research, reference, documents, and data which relevant. An accidental sampling technique is used to take 15 Dukcapil offices. Next, secondary data was collected, and analyzing data used qualitative descriptive technique to identify an innovation of Adminduk service. The result of this study showed, the Adminduk service innovations during the Covid-19 pandemic, in 3 (three) types, covering an online application, Covid-19 health protocols, and pickup the ball innovation. The Dukcapil offices are relevant need to copy an Adminduk service innovation alternative types, with accordance according to local condition, for overcome the Covid-19 pandemic constraints, and use them as input for public service can be function in the new-normal era.